Escherichia coli O157:H7 Bacteria Antibiotic Resistant Isolated from Flies at Food Courts in IPB Dramaga Campus - Aminudin, Muhammad Rizki; Lukman, Denny Widaya; Sudarwanto, Mirnawati Bachrum; Pisestyani, Herwin (Jurnal Sain Veteriner, 2024)
Several human and animal pathogens transmit into the food chain through houseflies as mechanical vectors, one of which is E. coli O157:H7. E. coli O157:H7 can express Shiga toxin (Stx) which can cause diarrhea, hemorrhagic colitis, and potentially fatal hemolytic-uremic syndrome (HUS) in humans. Some pathogen strains show resistance against various antibiotics, causing complex health problems. This study aims to analyze the presence of antibiotic-resistant E. coli O157:H7 bacteria carried by houseflies (M. domestica) in the food court IPB Dramaga campus area. Detection of E. coli O157:H7 on fly legs using qPCR method based on MU 7.2.3.32-8. E. coli O157:H7 isolates were tested for sensitivity to the antibiotic’s ciprofloxacin, ampicillin, tetracycline, trimethoprim-sulfamethoxazole, cefepime, chloramphenicol, ceftazidime, cefotaxime, and ceftriaxone using the Kirby Bauer disc diffusion method. This study isolated 5 E. coli isolates (5/40; 12.5%), and 2 of them were confirmed as E. coli O157:H7. One isolate of E. coli O157:H7 was resistant against ampicillin and tetracycline, and one isolate was resistant against ampicillin, tetracycline, trimethoprim-sulfamethoxazole, and ceftazidime. The multi-drug resistance was identified only in 1 isolate of E. coli O157:H7.Houseflies collected from the food court have the potential to transmit antibiotic-resistant E. coli O157:H7 around the IPB campus.